Ritual matters : dynamic dimensions in practice - Brosius, Christiane, 1966-; Husken, Ute. (New Delhi : Routledge, 2010)
Contributed articles.
Includes bibliographical references.
Keywords: Rites and ceremonies -- India; Ritual; India -- Religious life and customs